Business Strategy Formulation and Implementation Plan Of Choco'te Cafe - Fitrafsya, Rhamon; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2016)
Abstract - Culinary business are now growing rapidly especially in Bandung. This caused the rise of many resto and cafe in Bandung. One of them is Choco’te Cafe which presents chocolate beverages & cakes as a main products. The issue of Choco’te Cafe is they don’t have long-term planning. Beside that, their actual sales still below the target. Low barrier to entry industry makes the competition become thight, because many start-up company also involved in the competition. They have the problem in lack of marketing ability to promote their products. Particular problem also occur at internal operation and human resource. PEST(Political Economic Social Technological), Porter’s Five Forces Analysis and Competitor Analysis are used to analyze the external business environment. While Internal business environment is analyzed using VRINE Analysis and existing business model canvas. The output from external and intenal analysis will be used in SWOT Analyzer Framework to find the Company Positioning and Strategy. By this analyzer, Growth Strategy with Horizontal Growth concentration is the best alternative for Choco’te Cafe. Functional Strategy of Choco’te Cafe will be developed by TOWS Matrix, which is addressed into several functional areas. All of them will help the owner to visualize the strategies. This paper also propose new business model canvas to improve their business strategy more details. Strategy Formulation is developed for 5 years long range plan. Then the implementation plan are described in the detail, which is include program, budget and timeline. Keyword : Culinary Business, Cafe Concept, Start-up Company, Strategy Formulation